ANALYSIS OF RELATIONSHIP OF GENETIC HISTORY AND OBESITY WITH EVENT OF BREAST CANCER IN 2018 - Harahap, V.A Irmayanti (SCIENTIA JOURNAL, 2019)
ABSTRACT Breast cancer is a malignancy in breast tissue that can originate from the ductal epithelium or lobule. Breast cancer is one of the most common types of cancer in Indonesia. Specific causes of breast cancer are still unknown, but there are many factors that are thought to have an influence on the occurrence of breast cancer including: reproductive factors, hormone use, obesity, fat consumption, radiation, family history and genetic factors, mutation factors This research is a cross sectional study to determine the relationship of genetic history and obesity with the incidence of breast cancer at Raden Mattaher Jambi Hospital in 2018. Collecting data from medical records. The population in this study were all women who were treated in Raden Mattaher Jambi Hospital as many as 240 people with a sample of 45 people. This research has been carried out on 04 to 19 July 2018 which was held at RSUD Raden Mattaher Jambi. The sampling technique in this study was simple random sampling with a checklist sheet. Data analysis in this study used univariate and bivariate analysis in the form of tables and frequencies. The results of this study indicate that the results obtained from the genetic history of 45 people there were 23 (51.1%) people, the picture of obesity there were 25 (55.6%) people with obesity. Based on the results of the study obtained an overview of the incidence of breast cancer, from 45 people there were 24 (53.3%) people with breast cancer and 21 (46.7%) did not have breast cancer. There was a correlation between genetic history and breast cancer incidence in Raden Mattaher Jambi Hospital in 2018 with a p value of 0,000. There is a relationship between obesity and the incidence of breast cancer in Raden Mattaher Jambi Hospital in 2018 with a p-value of 0.002.  It is expected that health workers can provide input and information to in formulating a program policy to prevent breast cancer in women Raden Mattaher Jambi Hospital.   Keywords      : Breast Cancer, genetic history, obesity Reading List : 21 (2005-2018)